2022
DOI: 10.21203/rs.3.rs-1887294/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How does clean fuels and technologies-based energy poverty affect carbon emissions? New evidence from eighteen developing countries

Abstract: The relationship between all types of poverty and other socioeconomic indicators has been studied extensively; nevertheless, clean fuels and technologies-based energy poverty, which is adjusted for carbon emissions, have not been studied. The current study empirically examines the effect of clean fuels and technologies-based energy poverty on carbon emissions (Co2e) using panel data of eighteen developing countries from Asia for the period of 2006–2017. By using the System-Generalized Method of Movement (SGMM)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Sreenu et al [66] applied the ARDL and nonlinear autoregressive distributed lag models and reported that FDI flow into India was highly dependent on less stringent environmental protection laws during 1990-2020. Yahong et al [67] confirmed that GDP and population are associated with increased CO 2 e in Asian developing countries by employing the system-generalized method of movement during 2006-2017. Dkhili [68] observed a negative relationship between FDI and REC in Middle Eastern and North African countries during 1990-2018 by using the EKC hypothesis.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Sreenu et al [66] applied the ARDL and nonlinear autoregressive distributed lag models and reported that FDI flow into India was highly dependent on less stringent environmental protection laws during 1990-2020. Yahong et al [67] confirmed that GDP and population are associated with increased CO 2 e in Asian developing countries by employing the system-generalized method of movement during 2006-2017. Dkhili [68] observed a negative relationship between FDI and REC in Middle Eastern and North African countries during 1990-2018 by using the EKC hypothesis.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%